Food Calorie Scale Equipped with Daily Calorie Needs Analysis - Abidin, Muhammad Sainal; Kasih , Ridia Utami; Sutiari, Desak Ketut (STMIK Widya Cipta Dharma, 2024)
Humans require various types of nutritional intake to perform daily activities. The nutrients in food are converted into calories, which serve as a source of energy. Any calories not converted into energy are stored in the body as fat. Therefore, it is essential to monitor an individual's daily intake based on their caloric needs. Each type of food contains a different number of calories depending on its composition and quantity. Although numerous references provide calorie information for different foods, calculating the total daily calorie intake can be a complex process due to the variety of foods consumed. To simplify this process, a tool was developed to analyze daily calorie needs easily and efficiently. This tool uses a microcontroller to analyze and process data automatically, following a pre-programmed structure. The tool measures food weight using a load cell and incorporates a 4x4 keypad as an interface, making data entry more user-friendly. It is programmed to calculate the calorie content of 15 types of food based on their measured weight. The caloric value is determined by weighing the food and matching it with the programmed data. The measurement results showed a difference of 0.6 grams between the tool's weight measurement and the manufacturer's scale, with an R² value of 0.998, indicating high accuracy.